PENERAPAN METODE BERCERITA (STORYTELLING) DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS III MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Siti Aminah; Dede Indra Setiabudi; Iis Susiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low level of self-confidence among third-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun when speaking in front of the class. The research aimed to describe the strategies of implementing the storytelling method to enhance students’ self-confidence and to analyze the supporting and inhibiting factors in its application. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The participants consisted of teachers and third-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The findings revealed that storytelling created an interactive and enjoyable learning atmosphere, encouraging students to become more confident, courageous in performing, and able to express their ideas openly. Supporting factors included active teacher involvement, peer support, and a conducive classroom environment, while the inhibiting factors were limited time, varying student readiness, and the lack of diverse learning media. The study concludes that storytelling is an effective and applicable strategy to improve students’ self-confidence from an early stage, particularly in the context of Madrasah Ibtidaiyah. Keywords: Storytelling, Self- Confidence, Madrasah Ibtidaiyah